Knowledge intensive design technology : IFID TC5 /WG5.2 fifth workshop on knowledge intensive CAD, July 23-25, 2002, St. Julians, Malta - IFIP TC5/Wg5.2 Workshop on Knowledge Intensive CAD (5th : 2002 : St. Julians, Malta); Borg, Jonathan C.; Farrugia, Philip J.; Camilleri, Kenneth P.; International Federation for Information Processing (Boston : Kluwer Academic, 2004)
22